Bamako : An Engine of Growth and Service Delivery - World Bank Group (World Bank, Washington, DC, 2019)
This study focuses on Bamako, the capital of Mali, that dominates the country’s urban landscape. Acentral premise of policy-making in cities is that the flexibility, practicality, and focus of local governments make them ideal players to understand and respond to the needs of their citizens. Indeed, cities mostly aim their problem-solving at local conditions. In Mali, the economic importance of the capital city cannot be understated – it is the nerve center of the national economy. If the capital, Bamako, were to be removed, Mali would lose 36 percent of GDP. Thus, reforms and investments aimed at tackling urban development challenges in the capital will have knock-on effects on national economic development. This report also demonstrates how a variety of data could be used for urban innovations: opportunistic data, which is collected for one purpose and then used for another (such as data owned by cellphone companies and then used to understand urban mobility); purposely-sensed data, which is collected using cheap and ubiquitous sensors that can be deployed in public spaces (for instance, to better understand land and building use); and user-generated data, which comes from engaging people through social media platforms or crowdsourcing (for instance, through Open Street Map communities to track urban infrastructure investments and use). A summary of recommendations for unleashing Bamako’s potential includes coordinating land use and connective infrastructure, financing and managing better public service delivery, and investing in urban institutions.